2020
DOI: 10.1021/acs.energyfuels.0c00709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Silica and Cellulose Stationary Phases to Analyze Bitumen by High-Performance Thin-Layer Chromatography Coupled to Laser Desorption Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Bitumen is a complex mixture corresponding to the residue of the vacuum distillation of crude oil. It can be separated on the basis of polarity and solubility with saturates, aromatics, resins, and asphaltenes (SARA) fractionation. High-performance thin-layer chromatography is suited to analyze complex mixtures such as petroleum products, which separates compounds according to their polarity. In this work, the direct coupling between HPTLC and laser desorption ionization (LDI) Fourier transform ion cyclotron r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Pyrolysis oils are described as complex mixtures and ultrahigh-resolution mass spectrometry is required to have an advanced molecular description . Fourier transform ion cyclotron resonance (FTICR) mass spectrometers with a high magnetic field offer the best performances in terms of resolution, mass accuracy, and dynamic range. Over the past 20 years, it has been widely used to decipher ultracomplex mixtures. In the case of plastic pyrolysis oil, two studies using FTICR-MS reported their molecular characterization with atmospheric pressure photoionization (APPI). This enabled the characterization of hydrocarbon compounds and a part of oxygenated compounds defined as alcohols. , However, as stated before, the molecular characterization of other heteroatom-containing species such as nitrogen species is also important in order to anticipate their impact on the refining process. Depending on the ionization method, different ionization selectivities can be obtained in order to detect specific families of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis oils are described as complex mixtures and ultrahigh-resolution mass spectrometry is required to have an advanced molecular description . Fourier transform ion cyclotron resonance (FTICR) mass spectrometers with a high magnetic field offer the best performances in terms of resolution, mass accuracy, and dynamic range. Over the past 20 years, it has been widely used to decipher ultracomplex mixtures. In the case of plastic pyrolysis oil, two studies using FTICR-MS reported their molecular characterization with atmospheric pressure photoionization (APPI). This enabled the characterization of hydrocarbon compounds and a part of oxygenated compounds defined as alcohols. , However, as stated before, the molecular characterization of other heteroatom-containing species such as nitrogen species is also important in order to anticipate their impact on the refining process. Depending on the ionization method, different ionization selectivities can be obtained in order to detect specific families of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid quadrupole FT-ICR instrument (SolariXR, Bruker Daltonics, Bremen, Germany) equipped with a 12 T superconducting magnet was equipped with an LDI/MALDI source with a Nd:YAG × 3 solid-state laser (355 nm) . Broadband mass spectra were acquired over a mass range of m / z 147–1000 with an accumulation of 200 scans.…”
Section: Methodsmentioning
confidence: 99%
“…MALDI FT-ICR MS. A hybrid quadrupole FT-ICR instrument (SolariXR, Bruker Daltonics, Bremen, Germany) equipped with a 12 T superconducting magnet was equipped with an LDI/MALDI source with a Nd:YAG × 3 solid-state laser (355 nm). 30 Broadband mass spectra were acquired over a mass range of m/z 147−1000 with an accumulation of 200 scans. The signal was digitalized with 8 M points, resulting in a transient length of 3.4 s; this gave a resolving power number of 0.9 × 10 6 at m/z 400.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Rodgers et al used a similar approach by considering the modified aminopropyl silica (MAPS) fractionation of bitumen [181]. Lacroix-Andrivet et al used another methodology by combining high-performance thin-layer chromatography (HPTLC) and laser desorption-ionization (LDI) FT-ICR MS to analyze bitumen [182]. The HPTLC of bitumen on cellulose with a heptane/ethanol solvent mixture ensured the separation of maltenes and asphaltenes.…”
Section: Towards a Quantitative Approach To Petroleomic Datamentioning
confidence: 99%